2014
DOI: 10.2175/106143014x14062131177836
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation of Vertical Linear Motion Mixing in Anaerobic Digester Tanks

Abstract: Computational fluid dynamics (CFD) was used to simulate the mixing characteristics of a small circular anaerobic digester tank (diameter 6 m) equipped sequentially with 13 different plunger type vertical linear motion mixers and two different type internal draft-tube mixers. Rates of mixing of step injection of tracers were calculated from which active volume (AV) and hydraulic retention time (HRT) could be calculated. Washout characteristics were compared to analytic formulae to estimate any presence of parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The recirculation pump alone consumed 66% of the total mixing energy cost to pump mixed liquor between the bioreactor tank and the membrane tank in addition to mixing the bioreactor contents. The pilot-scale bioreactor design was not optimized for efficient mixing, and improvements in mixing energy consumption are possible by using alternative methods such as vertical linear motion mixers, which have successfully reduced the mixing energy consumption in anaerobic digesters. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recirculation pump alone consumed 66% of the total mixing energy cost to pump mixed liquor between the bioreactor tank and the membrane tank in addition to mixing the bioreactor contents. The pilot-scale bioreactor design was not optimized for efficient mixing, and improvements in mixing energy consumption are possible by using alternative methods such as vertical linear motion mixers, which have successfully reduced the mixing energy consumption in anaerobic digesters. , …”
Section: Resultsmentioning
confidence: 99%
“…The pilot-scale bioreactor design was not optimized for efficient mixing, and improvements in mixing energy consumption are possible by using alternative methods such as vertical linear motion mixers, which have successfully reduced the mixing energy consumption in anaerobic digesters. 49,50 Figure 4. Graph of power consumed and generated from equipment and processes of the system during a period where operating conditions were held relatively constant from days 420−445.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…The use of CFD models (openFOAM, Ansys, COMSOL) enables prediction of flow fields and turbulent mixing to the various levels of detail. A large number of studies have shown that CFD is a powerful tool for analysing and optimising particular water treatment processes, such as optimization of ozone contactors for microbial inactivation [60], [61], disinfection performance of UV reactors [62], oxidation processes [63], investigation of electrochemical variables in the operation of a continuous upflow electrocoagulation process in treating textile wastewater [64], simulation of the grit and sand separation effectiveness of a typical hydrodynamic vortex separator (HDVS) system [65], simulation of mixing characteristics of a small circular anaerobic digester tank [66], working performance of closed-loop bioreactor [67][66], verification of compliance of a water reclamation plant disinfection stage with respect to modal time [68], or analysing efficiency of the electrocoagulation (EC) process with stainless-steel electrodes for total nitrogen removal [69].…”
Section: Numerical Modellingmentioning
confidence: 99%
“…This is why impellers are installed more frequently. There are also other methods for ensuring agitation in digesters, e.g., draft-tube mixers [25,26]. In some cases, the agitation is caused just by the inlet flow recirculation depending on the geometry [27].…”
Section: Introductionmentioning
confidence: 99%